PENGARUH KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS MAHASISWA PROGRAM STUDI MANAJEMEN - Putra Buana (Jurnal Bina Bangsa Ekonomika, 2022)
This study aims to determine the effect of product quality and costumer satisfaction on student loyalty. This type of research is quantitative research sample of 78 students majoring in management on the campus of STIE "KBP" Padang using non probability samping by selecting research objects that are selective with determining several criteria. Analysis of the data used is multiple linear regression analysis, classic assumption test, and hypothesis testing. The results showed that product quality variables and costumer satisfaction affect consumer loyalty. The conclusion is that the better quality of the product and also if the costumer satisfaction level is high, it will increase student loyalty on using Xiaomi Smartphone products